Mathematical Modelling of Vehicle Rear End Design Using The Polynomial Response Surface Method (PRSM) - Kausalyah Venkatason,; Walferd Cornell,; Shasthri Sivaguru, (International Journal of Integrated Engineering, 2024)
It is important to consider the aerodynamic efficiency of the car in design as it improves fuel consumption and provides a smoother ride for the occupant. Studies have shown that vehicle front end profile affects the aerodynamic efficiency of a car but however, to date rear-end vehicle parametric studies have not been done to ascertain the influence of these parameters on the vehicle’s aerodynamic efficiency. This research presents the aerodynamic study of the sedan vehicle rear end by identification of the key vehicle rear-end parameters that influence the drag coefficient value of the vehicle model through the Polynomial Response Surface Modelling (PPRSM.). A total of 100 sedan vehicle models with 7 key rear end parameters generated through the Central Composite Design (CCD) sampling technique are designed using the CAD software, CATIA V5 R20. The front end of the vehicle profile is kept constant. Computational Fluid Dynamic Analysis (CFD) is then performed on these models to obtain the drag coefficient (Cd). Mathematical modelling is performed on the Cd data obtained using the PRSM method. The results from the PRSM model gave a value of R^2 is 0.926 with a relatively small error of RMSE at 0.006986 indicating a very good model fit. The rear end vehicle parameter that notably influenced the drag coefficient is the wind shield angle (X6) with the value from 21° to 41°. In conclusion, the rear end vehicle parameters do not seem to largely contribute to the aerodynamic stability of the model.